Issues and challenges in the implementation of micro-credential language courses: educators’ perspectives - Lip, Rashidah; Salam, Sazilah; Mohamad, Siti Nurul Mahfuzah; Mohd Yusoff, Azizul; Shabarudin, Muhammad Syahmie; Musa, Mohd Kamaruzaman; Dewi, Laksmi; Khoirunnisa, Azizah Nurul (Intelektual Pustaka Media Utama, 2025)
Micro-credential language courses have gained significant attention in the field of language education due to their potential to offer targeted and flexible learning experiences. However, the successful implementation of these courses relies on understanding the perceptions of language educators and addressing the associated issues and challenges. This study aims to identify language educators’ perceptions of online language learning platforms and micro-credential online language learning platforms and explore the issues and challenges in developing micro-credential language courses. Employing a quantitative approach, data was collected from 30 respondents from language educators at the centre for language learning, in a public university in Malaysia. Through survey questionnaires, quantitative insights into educators’ perceptions and experiences were gathered. The survey questionnaire gathered quantitative data on educators’ perceptions and experiences. This research sheds light on language educators’ perceptions of online language learning platforms and micro-credentials while identifying the challenges inherent in developing such courses. The findings underscore the significance of addressing these challenges to ensure the effective implementation of micro-credential-based language courses within online education contexts.